CURRENT METHODS IN ISOLATION OF HEMATOPOIETIC STEM CELL - Nilgün Okşak; Dürdane Serap Kuruca (İstanbul Tıp Fakültesi Dergisi)
Hematopoietic stem cells are the rare cells in various hematopoietic organs which are found in small numbers (1-100/ml). When these cells are transferred to patients suffering from diabetes, cancer, heart diseases, muscle and joint problems, they will help the patients’ bodies with the regeneration of impaired tissues. While the most important problem in the transplantation of autologous stem cells is malignant cell contamination in cancer patients, in allogeneic transplantation, it is immune reactions and tissue rejections. Therefore, clearing of the transplant material from tumour cells and immune cells may support the long-term healthy regeneration of the tissue to which they are transplanted. Although various techniques have been developed for the purification of these cells in terms of clinical use over many years, there is still no sufficiently effective method. In recent years, researchers have shown an increased interest in microfluidic systems because they are easy to use, cheap and highly efficient. In these types of systems designed with various microcapillaries, micropillars and micropores; purification is carried out according to the properties of cells such as size, deformability, cell adhesion and electrical charges. This review aims to explain traditional and emerging hematopoietic stem cell isolation methods and their advantages and disadvantages.